Business Cycles in the Run of History - Aimar, Thierry; Bismans, Francis; Diebolt, Claude (SpringerBriefs in Economics, 2016)
This book analyzes the development of economic cycles in the run of history. The focus is on the development of cycle theory, with maximum emphasis upon ideas. Chapter 1 delivers an overview of the debate about cycles before the 1970s. Chapter 2 completes this survey by presenting the main empirical investigations since that time. Finally, Chapters 3 and 4 illustrate the discourse, by presenting, in the tradition of Burns and Mitchell, original case studies on France, South Africa, and Germany.